2018
DOI: 10.1093/bioinformatics/bty233
|View full text |Cite
|
Sign up to set email alerts
|

Training for translation between disciplines: a philosophy for life and data sciences curricula

Abstract: MotivationOur society has become data-rich to the extent that research in many areas has become impossible without computational approaches. Educational programmes seem to be lagging behind this development. At the same time, there is a growing need not only for strong data science skills, but foremost for the ability to both translate between tools and methods on the one hand, and application and problems on the other.ResultsHere we present our experiences with shaping and running a masters’ programme in bioi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Despite the increasing significance of data scientists in today’s society, there is still a noticeable lack of clarity regarding the exact skills and expertise these professionals posses [ 5 , 6 ]. One reason for this is that the master programs that train students to become data scientists differ greatly in curriculum and focus [ 5 , 7 , 8 ]. For example, the skills gained from a biomedical data science program may vastly differ from those acquired in a marketing analytics program.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the increasing significance of data scientists in today’s society, there is still a noticeable lack of clarity regarding the exact skills and expertise these professionals posses [ 5 , 6 ]. One reason for this is that the master programs that train students to become data scientists differ greatly in curriculum and focus [ 5 , 7 , 8 ]. For example, the skills gained from a biomedical data science program may vastly differ from those acquired in a marketing analytics program.…”
Section: Introductionmentioning
confidence: 99%
“…Competencies include a combination of biology, understanding of technologies, statistics, and computational methods in addition to teamwork, communication, and the scientific discovery process. Also, researchers have found that while learning the breadth of biology, computation, and math, it is important to start early and maintain depth and focus on a multidisciplinary topic (Anton Feenstra et al, 2018). Thus, it is concluded a series of courses, if not whole training program, is needed to effectively train students in bioinformatics.…”
Section: Introductionmentioning
confidence: 99%